The Influence Of Profitability And Financial Leverage On Earnings Management And Its Impact On The Value Of Manufacturing Companies In The Indonesian Stock Ex-change (Case Study Of The Automotive Sub-Sector Period 2018-2022) - Arif Iman Santoso; Solihin Solihin (Green Publisher Indonesia, 2024)
The practice of income smoothing still occurs in the Indonesian economy. There are sever-al cases of income smoothing that have occurred, including at PT. Kimia Farma Tbk, PT and Lippo Tbk where these companies have published different financial reports. The purpose of this research is to determine the direct effect of profitability on income smoothing, fi-nancial leverage on income smoothing, profitability on company value, financial leverage on company value, the indirect effect of profitability on company value through income smoothing, financial leverage on company value through income smoothing and Income smoothing has a direct effect on company value. This research uses a mixed method. The population used in this research is automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling method is to use a purposive sampling technique so that the samples obtained are 50 samples. The re-search results show that there is no direct influence of profitability on income smoothing, there is no direct influence of financial leverage on profit smoothing, there is a direct influ-ence of profitability on firm value, there is no direct influence of financial leverage on firm value, there is no indirect influence income smoothing between profitability and company value, there is no indirect effect of income smoothing between financial leverage on com-pany value and there is no direct effect of income smoothing on company value.